The influence of brand trust customer experience and service innovation on customer loyalty (case study on berkah madani car rental) - Nurul Hasna Aninda Wardhani; Fansuri Munawar (Institute of Computer Science (IOCS), 2023)
This study aims to analyse the effect of brand trust, customer experience, and service innovation on customer loyalty. The results of this study are expected to be a source of knowledge for Berkah Madani in maintaining customer loyalty so that customers can make repeated rental transactions. This study uses sample of 100 people who are customers of Berkah Madani car rental in Bandung, West Java. Simple random sampling and distributing questionnaires are the sampling techniques used. A five-point Likert scale was used in measuring the research variables. The questionnaire was filled in by the respondent in accordance with the variable indicators. The data analysis method used is using SPSS for windows 21 software. Research shows that Brand Trust, Customer Experience and Service Innovation have a positive and significant effect on Customer Loyalty.